The importance of two-sided heterogeneity for the cyclicality of labour market dynamics - Ronald Bachmann; Peggy David (Institute for the Study of Labor (IZA), 2010)
Using administrative data on individual workers' employment history and firms, we investigate the cyclicality of worker flows on the German labour market. Focusing on heterogeneities on both sides of the labour market, we find that small firms hire mainly unemployed workers, and that they do so at the beginning of an economic expansion. Later on in the expansion, hirings more frequently result from direct job-to-job transitions to larger firms. Transitions between employment and unemployment at large firms are generally found to be more cyclical. However, this stylised fact disappears when the composition of the workforce is controlled for.
Keywords: J63; J64; J21; E24; 330; worker flows; accessions; separations; business cycle; job-to-job; employer-to-employer